TINJAUAN YURIDIS PEMASUKAN SATWA LIAR SECARA ILEGAL DI PELABUHAN PAREPARE MENU - Amiruddin; Muhammad Yunus Idy; Nasrul (Paulus Law Journal, 2023)
The phenomenon of increasing public interest in preserving endangered animals has an impact on environmental sustainability. One of the illegal actions carried out was sending endangered species through ports, one of which was Parepare Harbor. Law Number 21 of 2019 concerning Animal, Fish and Plant Quarantine was created to control this situation. This research aims to determine the legal action for illegal importation of wild animals at Paree-Pare Harbor. This research is normative legal research by reviewing statutory regulations, literature materials which are applied as rules or norms that are used and become the basis for everyone's actions. The results of the research show that the legal action for illegal entry of wild animals at Parepare Harbor is in accordance with the provisions of Law Number 21 of 2019. The legal action taken is in the form of imprisonment, fines and also administrative technical sanctions in the form of detention, rejection and destruction.